Missile Defense Roles in the Post-Cold War U.S. Strategy - Tomasz Pugacewicz (Ksiegarnia Akademicka Publishing, 2021)
The debate on missile defense in the United States has been going on for more than half a century, and brought about extensive literature on this subject. Although many studies on BMDS are publications dedicated to U.S. strategy, foreign and security policy, only a few works are focused solely on the U.S. missile defense strategy in the post-Cold War era from the long-term perspective. The aim of this article is to discuss the U.S. missile defense strategy in the post-Cold War era. The paper consists of an introduction, three sections, and a conclusion. The introduction includes short literature review and explains the domestic and international significance of BMDS. In the first section, BMDS is defined and described, next the ongoing debate about sources of U.S. focus on missile defense development is presented. In the last section, four functions of the BMDS in the U.S. post-Cold War strategy are analyzed. Conclusion includes brief recap, as well as costs and benefits assessment of the consequences of the BMDS deployment.